Venous thromboembolism and mortality in breast cancer: cohort study with systematic review and meta-analysis - Khan, Umair T.; Walker, Alex J.; Baig, Sadaf; Card, Tim R.; Kirwan, Cliona C.; Grainge, Matthew J. (BioMed Central, 2017)
Background Breast cancer patients are at an increased risk of venous thromboembolism (VTE). However, current evidence as to whether VTE increases the risk of mortality in breast cancer patients is conflicting. We present data from a large cohort of patients from the UK and pool these with previous data from a systematic review.